PENGARUH VARIASI MENU DAN DIGITAL MARKETING TEHADAP MINAT BELI KONSUMEN PADA KARSA KAFE PADANG - Fauzana, Helga Melosa; Asnur, Lise (Jurnal Daya Saing, 2023)
The purpose of this study is to describe and analyze menu variations, digital marketing and the influence of menu variations and digital marketing on the buying interest of Karsa Café Padang consumers. This type of research is quantitative with causal association methods. The population of this panel consists of consumers who enjoy various Karsa Café Padang menus with a sample of 100 people. Data was collected by distributing questionnaires with a Likert scale in the form of checklists. Test the device using validity and reliability tests. Data is processed with Microsoft Excel and SPSS version 26.00. Based on the results of this survey, the average respondent score for the menu variable was 0.67 with the category very good, the digital marketing variable 88.25 good, and the consumer buying interest variable 89.50 good. Menu variations have no significant effect on the dependent variable, namely Consumer Buying Interest. Digital marketing has a significant effect on the dependent variable, namely consumer buying interest. Keywords: influence, menu variation, digital marketing